Impact of COVID-19-Related Sports Activity Disruptions on the Physical Fitness of Japanese Adolescent Athletes - Hiromune Obayashi; Yasunari Ikuta; Naoki Nakashima; Ryoko Yamamoto; Hironori Fujishita; Koki Fukuhara; Tetsuhiko Sakamitsu; Kai Ushio; Hiroaki Kimura; Nobuo Adachi (MDPI AG, 2022)
We assessed whether the coronavirus disease 2019 (COVID-19) pandemic-related disruptions impacted the physical fitness of adolescent athletes. We reviewed the age-, sex-, and sports category-matched data of 78 adolescent athletes (divided into two groups: 2019 group = 37; 2020 group = 41) from the clinical database and investigated their height, weight, body composition, flexibility muscle strength, and jump height. We also provided questionnaires to the teams' coaches to collect data on the duration of practice suspension due to the COVID-19 pandemic; the practice hours per week in August 2019, immediately after the suspension ended, and in August 2020; and the guidelines for the players after resuming their practice. For data analyses, we considered p ≤ 0.05 as statistically significant. The strength of knee flexion and extension was significantly lower in the 2020 group than in the 2019 group; there was no difference in the other physical fitness parameters. The practice duration in August 2019 and August 2020 was the same. COVID-19-related interruptions did not alter the athletes' jump height, upper-limb strength, and flexibility but reduced lower-limb muscle strength. We recommend that basic strength training protocols be followed to prevent sports-related injuries after such unexpected practice interruptions.